KEBIJAKAN KEPALA SEKOLAH DALAM PENGAMBILAN KEPUTUSAN IMPLEMENTASI KURIKULUM MERDEKA - Rahayu, Ainun Frilia; Tresna Ayu Ratnapuri Zulfitri, Tresna Ayu Ratnapuri Zulfitri; Muhammad Iqbal Rahmat, Muhammad Iqbal Rahmat; Muchtarom, Muchtarom (Wali Pikir: Journal Of Education, 2024)
Leaders of educational institutions cannot be separated from policy and decision making. Policy and decision making are interrelated things. The school principal as the pillar of leadership in the elementary school education unit has a very big contribution to the smooth implementation of the independent curriculum. The approach used by researchers in this research is a qualitative approach. The method used is a qualitative descriptive method. In implementing the independent curriculum, school principals bear diverse and complex responsibilities, for example, school management activities which are very complicated and energy-consuming. School principals are required to be able to collaborate with various parties such as the teacher council, administrative staff, students, parents, and also the community around the school and together maximize the inventory owned by the school. The role of the principal in the implementation of driving schools includes the principal as planner, head schools as implementers, principals as supervisors, principals as leaders and principals as supervisors. Schools face various challenges both internal and external in implementing the independent curriculum.